Phylogenetic relationships of Hemiptera inferred from mitochondrial and nuclear genes. (1st November 2016) - Song, Nan; Li, Hu; Cai, Wanzhi; Yan, Fengming; Wang, Jianyun; Song, Fan
Abstract: Here, we reconstructed the Hemiptera phylogeny based on the expanded mitochondrial protein-coding genes and the nuclear 18S rRNA gene, separately. The differential rates of change across lineages may associate with long-branch attraction (LBA) effect and result in conflicting estimates of phylogeny from different types of data. To reduce the potential effects of systematic biases on inferences of topology, various data coding schemes, site removal method, and different algorithms were utilized in phylogenetic reconstruction. We show that the outgroups Phthiraptera, Thysanoptera, and the ingroup Sternorrhyncha share similar base composition, and exhibit "long branches" relative to other hemipterans. Thus, the long-branch attraction between these groups is suspected to cause the failure of recovering Hemiptera under the homogeneous model. In contrast, a monophyletic Hemiptera is supported when heterogeneous model is utilized in the analysis. Although higher level phylogenetic relationships within Hemiptera remain to be answered, consensus between analyses is beginning to converge on a stable phylogeny.